Foreign EFL Teachers’ Challenges and Strategies in Teaching English to Rural Thai Upper Secondary School Students - Ameliana Ameliana; I Rusamoh I-Saw; Noraisoh Kama (Prodi Pendidikan Bahasa Inggris, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Islam Darul Ulum Lamongan*, 2025)
Despite national initiatives to enhance English levels, current testing consistently shows that Thai students, particularly rural students, still experience low English proficiency. This study aimed to reveal foreign EFL teachers in rural Thai Secondary schools with particular emphasis on challenges and strategies within the English classroom. Based on a qualitative case study research design, data were collected through observation and in-depth interviews of EFL teachers at Assa-adah School in Southern Thailand. Findings revealed a set of interlocking challenge categories, including psychological (students with demotivation and anxiety), cognitive (students with low English proficiency), pedagogic (curriculum and practice gap, and limited access to media), and social challenges (students' parental environment, students' preference for translanguaging and teachers partnerless). The pedagogic strategies to overcome the challenges involve using responsive teaching and a fun learning method. The present study contributes to the ongoing debate on EFL instruction in Southeast Asia by way of illustrating the complex interdependence among sociocultural context, pedagogy, and governmental support. The implications of these findings are sought for the Thai policy maker to arrange continuous training among teachers and provide sufficient resources even in rural areas, as well as for English teachers in Thailand to anticipate the challenges encountered before classroom interaction.